Beyond varieties of capitalism - Bob, Hancké (Oxford University Press, 2007)
Thematically, the contributions to this volume are organized in four sections: how the macro-economics of EMU have influenced different European models of capitalism, how the Single Market programme was received in the different institutional regimes in European capitalism, how welfare and labor market reforms are debated and implemented, how European capitalism travelled east after 1989